Identification of the influence ofgas metal arc welding methods on the mechanical characteristics of duplex stainless steel - Bakhori, Ahmad; Yanhar, Muhammad Rafiq; Napid, Suhardi (Eastern-European Journal of Enterprise Technologies, 2025)
This study evaluates the effect of various Gas Metal Arc Welding (GMAW) methods on the mechanical properties of duplex stainless steel. The main objective is to identify the most effective GMAW process parameters in improving the mechanical properties of the material, including tensile strength, hardness, and corrosion resistance. The results of this study provide valuable insights into improving the weld quality, mechanical properties, and durability of duplex stainless steels in high-performance environments and corrosive conditions. Industries such as oil and gas, shipbuilding and chemical processing can greatly benefit from these findings by adopting optimized GMAW parameters to produce stronger and more durable weld joints. The findings also highlight the significant impact of welding and heat treatment on the alloy’s mechanical properties. The strength of the control material was recorded at 811.47 MN/m2, whereas the welded samples exhibited strengths between 177.07 and 257.32 MN/m2. The impact energy of the control material was 162.70 J, while the welded samples showed values ranging from 38.64 J to 56.20 J. Additionally, the study reveals that stress relief heat treatment resulted in the highest strength (A3=331 MN/m2) compared to quenching in lubricating oil (A2=329 MN/m2) and neem oil (A1=222 MN/m2), although variations in material toughness were observed. The uniqueness of this research lies in its systematic approach in correlating GMAW parameters with changes in microstructure and mechanical properties. The distinctiveness of this research stems from its structured methodology in linking GMAW parameters to variations in microstructure and mechanical properties, facilitating the identification of optimal welding conditions